The Influence of Teachers’ Competence and School Management on Teachers’ Performance - Fitriyanti Fitriyanti; Syaiful Eddy; Suherman Suherman (Yayasan Sembilan Pemuda Indonesia, 2026)
This study examines the simultaneous and partial influence of teacher competence and school management on teacher performance at State Elementary Schools in Ilir Barat 1 District, Palembang. Using a quantitative descriptive method, data was collected via questionnaires from 229 teachers sampled from a population of 534 across 29 schools. Analysis involved normality, linearity, and multicollinearity tests, followed by correlation, regression, t-tests, and F-tests. The results confirm that both teacher competence and school management have a positive and significant effect on teacher performance, both partially and simultaneously. The novelty lies in quantifying their combined impact within this specific regional context. Practically, these findings underscore the need for integrated professional development and administrative training programs. The study’s contribution is empirical evidence for educational policymakers and school leaders to prioritize holistic strategies that enhance both individual teacher capabilities and overarching managerial systems to improve overall educational outcomes.